2016
DOI: 10.1242/dev.140830
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-severing activity of the AAA+ ATPase Katanin is essential for female meiotic spindle assembly

Abstract: In most animals, female meiotic spindles are assembled in the absence of centrosomes. How microtubules (MTs) are organized into acentrosomal meiotic spindles is poorly understood. In Caenorhabditis elegans, assembly of female meiotic spindles requires MEI-1 and MEI-2, which constitute the microtubule-severing AAA+ ATPase Katanin. However, the role of MEI-2 is not known and whether MT severing is required for meiotic spindle assembly is unclear. Here, we show that the essential role of MEI-2 is to confer MT bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
8
23
1
Order By: Relevance
“…This in vitro work, together with our in vivo experiments, suggests that the preferred substrate of katanin complexes are sites where MTs interact with other MTs. Our findings are also consistent with an in vitro study showing a 1:1 stoichiometry MEI‐1:MEI‐2 within the katanin complex, which was suggested to be a hexamer of MEI‐1/MEI‐2 heterodimers (Joly et al , ). Based on the physical interaction between the N‐terminal microtubule interacting and trafficking domain of p60 and the C‐terminus of p80, the crystal structure of the mouse p60N/p80C heterodimer was recently resolved, providing the structural basis for formation of the p60/p80 heterodimer (Jiang et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…This in vitro work, together with our in vivo experiments, suggests that the preferred substrate of katanin complexes are sites where MTs interact with other MTs. Our findings are also consistent with an in vitro study showing a 1:1 stoichiometry MEI‐1:MEI‐2 within the katanin complex, which was suggested to be a hexamer of MEI‐1/MEI‐2 heterodimers (Joly et al , ). Based on the physical interaction between the N‐terminal microtubule interacting and trafficking domain of p60 and the C‐terminus of p80, the crystal structure of the mouse p60N/p80C heterodimer was recently resolved, providing the structural basis for formation of the p60/p80 heterodimer (Jiang et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings support the idea that katanin and TPX2 are important spindle length control and assembly factors in Xenopus . Katanin‐mediated microtubule severing activity has been shown to regulate spindle size in several organisms, including Caenorhabditis elegans , Xenopus , and human cells (Jiang et al, ; Joly, Martino, Gigant, Dumont, & Pintard, ; Loughlin et al, ; McNally, Audhya, Oegema, & McNally, ), which is consistent with results from meiotic spindle assembly simulations showing that altering microtubule depolymerization rates robustly scales spindle length (Loughlin et al, ).…”
Section: Resultssupporting
confidence: 71%
“…Although the role of KATANIN 1 in the male and female gametogenesis is emerging in animal systems (O’Donnell et al, 2012; Joly et al, 2016; Tang et al, 2016) such function has not yet been found in plants. Future detailed genetic studies might eventually shed more light on gametophytic defects in the KATANIN 1 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In animal systems recent studies have shed light into the role of katanin severing complex during the female meiotic spindle assemby (Joly et al, 2016) in Caenorhabditis elegans and during sperm production in mouse (O’Donnell et al, 2012). Additionally, katanin complex severing microtubules is under tight regulation during the transition form the meiotic to mitotic stage to allow proper embryogenesis, as its persistence could have detrimental effects (Beard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%